Cataract surgery for falls prevention and improving vision: modelling the health gain, health system costs and cost-effectiveness in a high-income country. Issue 4 (20th June 2019) - Boyd, Matt; Kvizhinadze, Giorgi; Kho, Adeline; Wilson, Graham; Wilson, Nick
Abstract : Aim: To estimate the health gain, health system costs and cost-effectiveness of cataract surgery when expedited as a falls prevention strategy (reducing the waiting time for surgery by 12 months) and as a routine procedure. Methods: An established injurious falls model designed for the New Zealand (NZ) population (aged 65+ years) was adapted. Key parameters relating to cataracts were sourced from the literature and the NZ Ministry of Health. A health system perspective with discounting at 3% was used. Results: Expedited cataract surgery for 1 year of incident cases was found to generate a total 240 quality-adjusted life years (QALYs) (95% uncertainty interval (UI) 161 to 360) at net health system costs of NZ$2.43 million (95% UI 2.02 to 2.82 million) over the remaining lifetimes of the surgery group. This intervention was cost-effective by widely accepted standards with an incremental cost-effectiveness ratio (ICER) of NZ$10 600 (US$7540) (95% UI NZ$6030 to NZ$15 700) per QALY gained. The level of cost-effectiveness did not vary greatly by sex, ethnicity and previous fall history, but was higher for the 65–69 age group compared with the oldest age group of 85–89 years (NZ$7000 vs NZ$14 200 per QALY gained). Comparing cataract surgery with no surgery, the ICER was even more favourable at NZ$4380 (95% UI 2410 to 7210) per QALY. Considering only the benefits for vision improvement and excluding the benefits of falls prevention, it was still favourable at NZ$9870 per QALY. Conclusions: Expedited cataract surgery appears very cost-effective. Routine cataract surgery is itself very cost-effective, and its value appears largely driven by the falls prevention benefits.